Students' Life Experiences and the Meaning of Conformity Behind the Boarding School Doors - Nur Saidah; Moersito Wimbo Wibowo; Mohamad Iksan (Eduvest - Journal of Universal Studies, 2025)
Pesantren, as traditional Islamic educational institutions in Indonesia, create unique environments where Santri (students) navigate complex social dynamics and behavioral expectations. Understanding conformity in these settings is crucial for developing educational approaches that balance religious character formation with individual well-being. This research examines the life experiences of Santri and the meaning of conformity in the Pesantren environment of Lembaga Tinggi Pesantren Luhur Malang (LTPLM). Involving nine Santri with a minimum stay of two years, this study employed a descriptive phenomenological approach through in-depth interviews and participatory observation. The results showed that conformity includes adherence to rules, acceptance of Pesantren values, and cultural adaptation, which support the strengthening of religious identity and the learning of social values. The findings also revealed challenges such as social pressure to conform and the potential for negative behavior due to the culture of seniority. This study concludes that conformity in Pesantren serves as a profound learning process for Santri character building. The implication of this research is the need for adaptive educational policies to minimize the negative impacts of conformity while supporting the development of socially and spiritually balanced Santri.